Skeletal remains from the territory of the Royal Castle in Warsaw - Szukiewicz, Hanna; Zarzycka, Danuta (Anthropological Review, 1975)
In 1972 and 1973 near castern façade of the Royal Castle in Warsaw under the floor of the Ball Hall was found an ossuary containing skeletal remains of at least six individuals; near southern ryzalit two skulls and in the vicinity of Great Manor two incomplete skeletons lying on the primordial layer were uncovered. All skeletal remains belonged to males, in two cases sex determinations are uncertain due to the scarcity of available diagnostic characters. Skeletons are robust with strongly markcd muscle attachements. Stature estimated on the basis of measurement of bones is high or intermediate. Skulls are long or very long. high with broad or mildly broad foreheads, mildly broad faces and high orbits. In connection with historical data it may be concluded that described skeletons most probably belonged to soldiers of Swedish army which conquered Warsaw in 1656.